2021
DOI: 10.1101/2021.03.28.437425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A TBP-independent mechanism for RNA Polymerase II transcription

Abstract: Transcription by RNA Polymerase II (Pol II) is initiated by the hierarchical assembly of the Pre-Initiation Complex onto promoter DNA. Decades of in vitro and yeast research have shown that the TATA-box binding protein (TBP) is essential to Pol II initiation by triggering the binding of other general transcription factors, and ensuring proper Pol II loading. Here, we report instead that acute depletion of TBP in mouse embryonic stem cells (mESCs) has no global effect on ongoing Pol II transcription. Surprising… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 114 publications
(168 reference statements)
0
14
1
Order By: Relevance
“…Our data indicate that most TATA‐less promoters are independent of TBP and utilize TRF2, or TBP and TRF2 in a redundant fashion. Transcription in the absence of TBP has been observed for particular promoters (Wieczorek et al , 1998 ; Kwan et al , 2021 ) and cell types (Martianov et al , 2002 ; Gazdag et al , 2016 ), potentially involving TBP paralogs such as TRF2 in flies. Even though TRF2 has been reported to be unable to bind DNA directly (Rabenstein et al , 1999 ; Baumann et al , 2018 ), it may be recruited indirectly to promoters, potentially through interactions with TFIIA and/or TFIID (Baumann & Gilmour, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data indicate that most TATA‐less promoters are independent of TBP and utilize TRF2, or TBP and TRF2 in a redundant fashion. Transcription in the absence of TBP has been observed for particular promoters (Wieczorek et al , 1998 ; Kwan et al , 2021 ) and cell types (Martianov et al , 2002 ; Gazdag et al , 2016 ), potentially involving TBP paralogs such as TRF2 in flies. Even though TRF2 has been reported to be unable to bind DNA directly (Rabenstein et al , 1999 ; Baumann et al , 2018 ), it may be recruited indirectly to promoters, potentially through interactions with TFIIA and/or TFIID (Baumann & Gilmour, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some GTFs might not be required in all cells (Tyree et al , 1993; Ranish et al , 1999; Martianov et al , 2002; Cabart et al , 2011; Gazdag et al , 2016; Kwan et al , 2021) and/or GTF paralogs may regulate transcription in distinct cell types or at specific promoters (Akhtar & Veenstra, 2011; Duttke et al , 2014; Zehavi et al , 2015). The TBP‐related factors TBP2 (also known as TRF3) and TBPL1 (TRF2 in Drosophila ) have, for example, been implicated in transcription in early steps of mouse oocyte differentiation and during spermatogenesis, respectively (Zhang et al , 2001; Gazdag et al , 2016; Martianov et al , 2016; Yu et al , 2020), In Drosophila , Trf2 has been suggested to regulate the transcription of ribosomal protein genes, histone H1, and DPE motif‐containing promoters (Isogai et al , 2007; Wang et al , 2014; Baumann & Gilmour, 2017; Kedmi et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mouse, we recently showed that during oocyte growth, transcription is mediated by an oocyte-specific complex containing the TBP paralog TBPL2, lacking TBP and TAF proteins 72 . More strikingly, TBP and TBP paralogs independent transcription has been described during Xenopus development 73 and two recent studies in mESCs or in human HAP1 cells have shown that acute depletion of TBP has no major impact on Pol II transcription without compensation by a TBP paralog 74,75 .…”
Section: Transcription Initiation By Partial Tfiid Complexesmentioning
confidence: 99%
“…For example, inactivation or nuclear depletion of TBP in budding yeast has been shown to decrease the transcription activity of all three RNA polymerases (4)(5)(6)(7). In mammals, like mouse embryonic stem cells (mESCs) and human HAP1 cells, acute depletion of TBP resulted in no changes in Pol II occupancy and transcription, while Pol III-mediated occupancy and transcription of tRNAs was severely impacted (8,9). TBP has also been shown to facilitate reactivation of Pol II transcription following mitosis in mESCs (10), though such mitotic bookmarking function remains unclear for Pol I or III transcription.…”
Section: Introductionmentioning
confidence: 99%